The Role Of The Constitutional Court In Realizing A Democratic Law State Through State Administration In Indonesia - Diantika Chayani; Arif Wibowo (JUSTICES: Journal of Law, 2023)
The Constitutional Court was formed to guarantee the constitution as the highest law so that it can be upheld. The position of the Constitutional Court in the Indonesian constitutional system is as a state institution that carries out a judicial function in the competence of the object of constitutional cases. The existence of the Constitutional Court as guardian of the existing constitution in Indonesia is to strengthen the foundations of constitutionalism in the 1945 constitution with the aim of upholding law and justice. The main authority of the Constitutional Court is to review laws against the 1945 Constitution which is commonly known as judicial review. Another authority of the Constitutional Court, as an effort to structuring the relationship between state institutions and democratic institutions based on the principle of the rule of law. The Constitutional Court is also the interpreter of the constitution which is final and has a function as guardian of the constitution. So the decisions of the Constitutional Court as one of the higher institutions in Indonesia must consider democratic values and the constitutional rights of citizens or human rights (HAM) with the aim of upholding a fair law for all people.